Low-skilled labor migration in Tajikistan: Determinants and effects on expenditure patterns - Kristina Meier (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
It is often assumed that international labor migration from Tajikistan, while having no noticeable effects on investment (usually defined as medium and long-term con- sumption, such as education, or investment into housing or business), on average leads to an increase in short-term consumption, mostly food. In this paper, a simple household-level model determining the migration decision is developed and tested empirically. In a second step, the effect of low-skilled labor migration on household expenditure shares is analyzed using 2SLS. While only weak effects of migration measured by a simple dummy are visible, repeating the analysis using the length of the migration spell instead, as well as its squared term, reveals that labor migration apparently takes a while to "kick in" and become profitable to those remaining at home. The observed long-term effects on household consumption patterns, albeit being rather small, actually speak in favour of investment of remittances, with the respective shares increasing over time, while the budget share spent on food slowly decreases.
Keywords: J61; F22; I31; 330; labor migration; remittances; consumption shares; Tajikistan